Acute porphyrias – A neurological perspective. Issue 11 (17th October 2021) - Gerischer, Lea M.; Scheibe, Franziska; Nümann, Astrid; Köhnlein, Martin; Stölzel, Ulrich; Meisel, Andreas
Abstract: Acute hepatic porphyrias (AHP) can cause severe neurological symptoms involving the central, autonomic, and peripheral nervous system. Due to their relative rarity and their chameleon‐like presentation, delayed diagnosis and misdiagnosis are common. AHPs are genetically inherited disorders that result from heme biosynthesis enzyme deficiencies and comprise four forms: acute intermittent porphyria (AIP), variegate porphyria (VP), hereditary coproporphyria (HCP), and ALA‐dehydratase porphyria (ALADP). Depending on the clinical presentation, the main differential diagnoses are Guillain‐Barré syndrome and autoimmune encephalitis. Red flags that could raise the suspicion of acute porphyria are neurological symptoms starting after severe (abdominal) pain, in association with reddish urine, hyponatremia or photodermatitis, and the presence of encephalopathy and/or axonal neuropathy. We highlight the diagnostic difficulties by presenting three cases from our neurological intensive care unit and give a comprehensive overview about the diagnostic findings in imaging, electrophysiology, and neuropathology. Abstract : Acute hepatic porphyrias (AHP) can cause severe neurological symptoms involving the central, autonomic and peripheral nervous system. Due to their relative rarity and their chameleon‐like presentation awareness among neurologists is low and delayed diagnosis and misdiagnosis are common. Red flags that should raise the suspicion of acute porphyria are neurological symptoms starting after severe (abdominal) pain, in association with reddish urine, hyponatremia or photodermatitis and the presence of encephalopathy and/or axonal neuropathy.